TQM training for state / Central training institutions - Agnihotri, V. K. (Mussoorie, 1998)
The TQM Training Project for Government Training Institutions sponsored by the Department of Personnel and Training, Government of India and the Department for International Development, UK (through the British Council Division), inter alia envisages a range of monitoring activities during the Project cycle.
Keywords: Total quality management